MOTHERHOOD AND CAREER PROGRESSION: THE IMPACT OF MATERNITY LEAVE ON WOMEN IN FINANCE AND ECONOMICS-RELATED SPHERES IN ASTANA - Bayanova, Anel (Nazarbayev University School of Sciences and Humanities, 2025)
This study explores how maternity leave affects the career trajectories of women working in finance and economics-related sectors in Astana, Kazakhstan. Drawing on ten semi-structured interviews with both mothers and non-mothers, the research examines how factors such as the length of leave, workplace flexibility, financial support, and cultural expectations shape women’s professional outcomes. Findings show that short, flexible leaves combined with remote work and family support allow some women to maintain career momentum, while longer absences often result in missed promotions, skill gaps, and financial dependency. However, these outcomes are not solely determined by personal choices but are influenced by systemic and cultural conditions such as limited childcare, rigid organizational norms, and gendered expectations. This study contributes to understanding the nuanced ways in which maternity leave intersects with gender inequality in Kazakhstan's labor market and underscores the need for more inclusive work-family policies.
Keywords: Maternity Leave; Motherhood Penalty Career Progression Gender Inequality Work-Family Balance Finance and Economics Kazakhstan Workplace Flexibility Childcare Policy Women in the Workforce; Career Progression; Gender Inequality; Work-Family Balance; Finance and Economics; Kazakhstan; Workplace Flexibility; Women in the Workforce; Childcare Policy; type of access: embargo